2020
DOI: 10.1002/adbi.202000143
|View full text |Cite
|
Sign up to set email alerts
|

Modulating T Cell Activation Using Depth Sensing Topographic Cues

Abstract: This report examines how sensing of substrate topography can be used to modulate T cell activation, a key coordinating step in the adaptive immune response. Inspired by the native T cell–antigen presenting cell interface, micrometer scale pits with varying depth are fabricated into planar substrates. Primary CD4+ T cells extend actin‐rich protrusions into the micropits. T cell activation, reflected in secretion of cytokines interleukin‐2 and interferon gamma, is sensitive to the micropit depth. Surprisingly, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…While microstructured surfaces were shown to induce formation of membrane protrusions in T cells, [16][17][18] T cells reside in nanostructured environments, where they explore the nanoscale features of antigen presenting cells. To match with the membrane protrusions used by T cells, we studied the effect of nanotopographical constraints on microvilli formation in non-activated T cells.…”
Section: T Cell Microvilli Induction and Stabilization By Nanoporous Substratesmentioning
confidence: 99%
“…While microstructured surfaces were shown to induce formation of membrane protrusions in T cells, [16][17][18] T cells reside in nanostructured environments, where they explore the nanoscale features of antigen presenting cells. To match with the membrane protrusions used by T cells, we studied the effect of nanotopographical constraints on microvilli formation in non-activated T cells.…”
Section: T Cell Microvilli Induction and Stabilization By Nanoporous Substratesmentioning
confidence: 99%
“…Myoblasts are typical anchoring-dependent cells, and their interaction with the microenvironment plays a crucial role in cellular behavior regulation and functional maintenance. Myoblasts are immersed in a complex microenvironment composed of various chemical and physical cues. Among these cues, substrate topography has been proven to exert a profound influence on various cell behaviors, including orientation, migration, polarization, adhesion, and so on. Many studies have been devoted to exploring the regulatory effects of topological patterns on cell behavior. , For example, micropillar arrays can change substrate stiffness and affect cell elongation and spreading, while the shape and size of microwells can determine cell morphology . For muscle tissue regeneration, the uniform orientation of myoblasts plays a crucial role in ensuring the structural and functional integrity of muscle tissue. Therefore, to achieve skeletal muscle regeneration in vitro, it is urgent to explore the influence of topological cues on the orientation regulation of myoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed the guiding role of interactions between cells and extracellular matrix (ECM) in regulating cellular behaviors. [8][9][10][11][12][13] As a dynamic and hierarchically organized composite, ECM is a complex physiological system composed of multilevel structures down to cellular (micrometer) and subcellular (nanoscale). [14] The critical component for studying cell-microenvironment interactions is to create, characterize, and manipulate dynamic microenvironmental cues in vitro down to a cellular and subcellular length scale.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Recently, various biomaterial scaffolds have been created to study the interaction between cells and their surrounding microenvironment. [12][13][14][15][16][17][18] It was found that micro-or nanoscale features of substrates can affect cell adhesion, [19][20][21] differentiation, [22,23] proliferation, [24][25][26][27] migration, [28][29][30][31] morphology, [32,33] alignment, [34][35][36][37] and cytoskeleton organization. [38] Microscaled features influence cell growth through the alignment of cells with topographical features by the contact guide.…”
Section: Introductionmentioning
confidence: 99%